Citizens' attitudes towards technological innovations: The case of urban air mobility - Kalakou, S.; Marques, C.; Prazeres, D.; Agouridas, V. (Technological Forecasting and Social Change, 2023)
Technological innovations and their enabled services support business growth and promise benefits for societies. In the mobility sector, technology adoption and its sustainable integration into current transport systems strongly depend on citizens' perspectives both as users and non-users. Following a bottom-up approach originating from the societal views, this study analyses the attitude of citizens towards Urban Air Mobility (UAM) and brings insights into the citizens' expectations of the role that UAM can play in inhabited environments. The views of 485 residents of Lisbon in Portugal were collected to address aspects of UAM receptiveness. Six clusters of citizens were obtained expressing different attitudes towards UAM: open-minded, pollution sensitive, first movers, emergency supporters, skepticals and deniers. The designated clusters require different policies and practices from the side of policymakers and transport operators. The results indicate that positive attitudes towards UAM are characterized by higher intention to use such services suggesting that actions need to be taken to better comprehend each cluster's expectations. The study sheds light on societal aspects of technology deployment and provides insights to UAM stakeholders for the sustainable inclusion of UAM in societies catering for all citizen-related topics and contributing to the development and diffusion of the UAM ecosystem.